2004
DOI: 10.2166/wst.2004.0214
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mass transfer and chemical reaction on ozonation of azo dyes

Abstract: Azo dyes can be only mineralised by chemical oxidation. In this paper the oxidation of Reactive Black 5 (RB 5) and Reactive Orange 96 (RO 96) with concentrations between 35 and 5,700 mgL(-1) (RB 5) and between 20 and 2,050 mgL(-1) (RO 96) was investigated in a lab-scale bubble column. The reactor was modelled for two cases, a completely mixed and a plug flow gas phase. The oxidation rate was influenced by mass transfer for all dye concentrations used. For low dye concentrations mass transfer alone was decisive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…Recently Vaidya and Kenig (2007) have reviewed the kinetic data present in the literature concerning this system observing significant discrepancies between the kinetic rate constants. Neither an agreement between different authors is found for example in the study of the oxidation of textile azo dyes with the ozone, a system with evident applications in environmental engineering (Liakou et al, 1997; Wu and Wang, 2001; Sevimli and Kinaci, 2002; Sevimli and Sarikaya, 2002; Choi and Wiesmann, 2004; Gokcen and Ozbelge, 2005). In a significant number of papers related with this problem, the kinetic rate constants are reduced to apparent pseudo‐first order rate constants which are not useful for reactor design, scale‐up or control purposes.…”
Section: Introductionmentioning
confidence: 95%
“…Recently Vaidya and Kenig (2007) have reviewed the kinetic data present in the literature concerning this system observing significant discrepancies between the kinetic rate constants. Neither an agreement between different authors is found for example in the study of the oxidation of textile azo dyes with the ozone, a system with evident applications in environmental engineering (Liakou et al, 1997; Wu and Wang, 2001; Sevimli and Kinaci, 2002; Sevimli and Sarikaya, 2002; Choi and Wiesmann, 2004; Gokcen and Ozbelge, 2005). In a significant number of papers related with this problem, the kinetic rate constants are reduced to apparent pseudo‐first order rate constants which are not useful for reactor design, scale‐up or control purposes.…”
Section: Introductionmentioning
confidence: 95%
“…For low dye concentrations, the mass transfer alone was decisive for the reaction rate showing no enhancement due to chemical reaction. However, in the region of high dye concentrations, the slope of the ozone concentration profile inside the liquid boundary layer increased with increasing dye concentrations as a result of a chemical oxidation (Choi and Wiesmann, 2004 (Neamţu, et al, 2004b).…”
Section: Advanced Oxidationmentioning
confidence: 98%
“…Liao et al [27] reported that dye solutions exposed to UV radiation only, achieved varying decolorization depending upon type of dye as well as UV intensities and contact time. Therefore, the UV degradation processes must be accompanied with oxidants/photocatalysts such as H 2 O 2 , TiO 2 or ozone to generate active hydroxyl radicals to initiate autooxidation reactions for complete degradation [28,29] . According to Feng et al [25] , addition of chemicals as oxidants could interfere with the process and thus recommended the application of dielectric barrier discharge (DBD) driven excimer lamps.…”
Section: −2mentioning
confidence: 99%